Representação De Infância Em Zalina Rolim: Entre A Arte Poética E A Educação - Santos, Fernanda Nunes Dos [UNIFESP] (2017)
This research work is a study about the book Livro das Crianças and the work of Zalina Rolim presented in the magazine Revista do Jardim da Infância, that are materials intended for the education of the children in São Paulo. The book Livro das Crianças was utilized in public schools of São Paulo, and the magazine had the Kindergarden children as recipients. The study of Zalina Rolim’s work concentrates in the understanding of how the childhood was represented in two specific items for the scholar use. For the review of childhood representation on those works, it was considered the historical context of São Paulo in the nineteenth century, once the book and the magazine were written in the final years of that century. The investigation regarding the personal path, as well as the work study of Zalina, destined to the school corroborates to the understanding of a childhood representation presented in children literature of the final years of nineteenth century. In the book Livro das Crianças the study was centered on the model that the school provided in that time: to civilize and educate. In the pedagogic work, the studies took place after the relevance Zalina gave during the narrations in the language classes, even as the toys and games, activities fulfilled through nursery rhymes and songs. The context the works were placed in refers to a national policy engaged in the children education; the intention consisted in removing the citizen from the ignorance he had been for decades. Therefore, by collating such work, the aim was to understand the childhood representation in the social and scholar context, considering the children a cultural being, likely to changes that occur over history. Based on the studies and reviews of the works we can understand that the pedagogic structure of Zalina’s work refers to the full development of the child that, if well educated, will become the ideal human being of the nation. The book is part of a literature that had the duty of civilize and educate the children to practice well the Brazilian citizen role, and the magazine was part of a context that inserted the small child in the school to look after his development.